2019
DOI: 10.15294/jdm.v10i2.19398
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Planned Behavior Approach and Gender Differences on Students’ Intention to Practice Online Business

Abstract: The purpose of this study is to examine the influence of attitude, subjective norm, perceived behavioral control, gender and self-efficacy towards college students' intention to practice online business in Surabaya. Theory of planned behavior is used to analyze student intention to become an entrepreneur through e-commerce especially online shop platform, thus becoming solution to decrease unemployment rate in Indonesia and furthermore increasing the economy of Indonesia in general. This research uses primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
(39 reference statements)
0
4
0
9
Order By: Relevance
“…Namun lain halnya dengan penelitian tersebut, penelitian ini juga melihat pengaruh entrepreneurship education pada dua jenjang yang berbeda yaitu sarjana dan vokasi, dengan mempertimbangkan bahwa vokasi memiliki matakuliah yang lebih spesifik pada kegiatan praktikum, yaitu praktikum kewirausahaan. Penelitian ini dilakukan juga dengan mengacu pada penelitian lain yang menunjukkan bahwa subjective norm dan perceived behavioral control memberikan pengaruh yang positif terhadap e-commerce intention (Suryawirawan, 2020) dan pengaruh positif attitude, subjective norm serta perceived behavioral control pada entrepreneurial intention (Dinc & Budic, 2016). Namun berbeda dengan penelitian diatas, penelitian ini mengikutsertakan variabel entrepreneurship education sebagai variabel moderasi yang diharapkan mampu meningkatkan pengaruh theory of planned behavior pada entrepreneurial intention.…”
Section: Entrepreneurial Intentionunclassified
“…Namun lain halnya dengan penelitian tersebut, penelitian ini juga melihat pengaruh entrepreneurship education pada dua jenjang yang berbeda yaitu sarjana dan vokasi, dengan mempertimbangkan bahwa vokasi memiliki matakuliah yang lebih spesifik pada kegiatan praktikum, yaitu praktikum kewirausahaan. Penelitian ini dilakukan juga dengan mengacu pada penelitian lain yang menunjukkan bahwa subjective norm dan perceived behavioral control memberikan pengaruh yang positif terhadap e-commerce intention (Suryawirawan, 2020) dan pengaruh positif attitude, subjective norm serta perceived behavioral control pada entrepreneurial intention (Dinc & Budic, 2016). Namun berbeda dengan penelitian diatas, penelitian ini mengikutsertakan variabel entrepreneurship education sebagai variabel moderasi yang diharapkan mampu meningkatkan pengaruh theory of planned behavior pada entrepreneurial intention.…”
Section: Entrepreneurial Intentionunclassified
“…However, some previous studies chose to exclude attitude from the model due to the weak role found (Abdullah et al, 2016;Bhatiasevi, 2011). Several recent studies found a strong relationship between the two variables (Almaimouni et al, 2014;Bennani & Oumlil, 2014;Hoque et al, 2015;Isaac et al, 2017;Suryawirawan, 2020). Thus, the relationship between attitude and e-commerce future adoption would still be further investigated.…”
Section: Attitudementioning
confidence: 96%
“…Female students have a higher intention to practice online business compared to male students [27]. This study shows that gender has a moderate effect on entrepreneurial intentions because of the enactment of Theory of Planned Behavior (subjective norms, perceived behavioral control and attitudes towards behavior) [28].…”
Section: Rq1: What Is the Relationship Between Gender And Intention?mentioning
confidence: 99%